2011
DOI: 10.4021/wjon322w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pain and Interference Patterns With Brief Pain Inventory in Patients With Bone Metastases: A Confirmatory Study

Abstract: BackgroundThis study investigates the validity of the psychometric properties of the Brief Pain Inventory (BPI) in patients with bone metastases and determines if patients with lower body pain exhibit higher levels of activity interference than those with upper body pain.MethodsThree hundred and eighty-six patients treated, between May 2003 and June 2007, for painful bone metastases were included in this analysis, 336 patients with complete data were included in further analyses. Cronbach’s Alpha, confirmatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Overall pain perception in all groups was very low, especially when compared with other pathologies measured with the BPI‐SF such as osteoarthritis of the hip and knee or a malignancy with bone metastases 26,31 . Others have also demonstrated that ear surgery in general can be considered to be near to painless 32 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Overall pain perception in all groups was very low, especially when compared with other pathologies measured with the BPI‐SF such as osteoarthritis of the hip and knee or a malignancy with bone metastases 26,31 . Others have also demonstrated that ear surgery in general can be considered to be near to painless 32 .…”
Section: Discussionmentioning
confidence: 94%
“…The Brief Pain Inventory–Short Form (BPI‐SF) was used to measure postoperative pain 25–27 . BPI‐SF is a validated pain questionnaire and uses a scale from 0 (no pain/influence) to 10 (worst pain/influence).…”
Section: Methodsmentioning
confidence: 99%
“…Pain seems to be a physical symptom of particular importance in patients with CD/FND as clinically significant levels of pain occur in 87.1% of the sample, and pain requiring medication occurs in more than 55% of the sample. Moreover, the mean BPI score is over 5, which is higher than the mean score reported in a study on cancer patients with bone metastases (Zeng et al, 2011). Stone and Sharpe find a high prevalence of pain in functional weakness (Stone, Warlow, & Sharpe, 2010), and possible interpretations of the association between chronic regional pain syndrome and CD/ FND have been discussed (Popkirov, Hoeritzauer, Colvin, Carson, & Stone, 2019).…”
Section: Summary Of Principal Findingsmentioning
confidence: 87%
“…However, the internal consistency in the three remaining studies showed no statistical significance (Cronbach’s α=0.04-0.943). The internal consistency of BPI was assessed in two studies, both of which provided adequate evidence (Cronbach’s α>0.7) 26 , 27 . Only one study assessed the internal consistency of SF-36 25 .…”
Section: Resultsmentioning
confidence: 99%